Effective task scheduling for heterogeneous distributed systems using firefly algorithm. (2015) - Eswari, R.; Nickolas, S.
Achieving minimum execution time for any application with better resource utilisation is a major challenge in heterogeneous distributed systems. But the performance can be exploited in these systems through proper scheduling of application tasks. An efficient meta-heuristic algorithm called firefly algorithm is applied in this paper to solve static task scheduling problem in heterogeneous systems. The social behaviour of fireflies is mimicked to generate optimal task schedule length. The efficiency of the firefly-based task scheduling algorithm is compared with the existing particle swarm optimisation-based scheduling algorithm. The experimental results show that the firefly algorithm-based approach gives better results when compared to PSO algorithm and performs well with minimum processors for effective scheduling of tasks.